A computer‐aided educational tool for vector control of AC motors in graduate courses. Issue 3 (16th April 2020) - Aktaş, Mustafa; Çavuş, Barış
Abstract: Analysis of dynamic behavior of alternating current (AC) motors and their vector control has an important place in the education of electrical and electronics engineering at the graduate level. Generally, only theoretical education in engineering affects motivation of both educators and students negatively. Particularly, in graduate education, realization of subjects of AC motors in laboratory facility enables students to learn effectively. However, it may not be easy to implement because of establishing cost of a physical laboratory environment in universities. Therefore, by using visual software technology, engineering applications such as vector control of AC motors can be prepared in a simulation tool and students' active learning skills can be developed without any cost by means of visual simulation studies. Hence, in this study, an educational interface was prepared as a simulation for vector control of AC motors by using MATLAB GUI. In this application, two types of AC motors (induction motor and permanent magnet synchronous motor) and two types of vector control (direct torque control and field‐oriented control) can be realized. In the simulation, after selecting motor and vector control type, determination of speed acquisition method and speed control method can be selected, and simulation study can be performed easily. Performance of selected motor type and control methods can be evaluated by using current, speed, torque, and energy consumed. In addition, to see success of the developed tool, it was used by the students at Ondokuz Mayis University, and at the end of lesson, a questionnaire was made and students' ideas were taken.